2016
DOI: 10.14744/anatoljcardiol.2016.6799
|View full text |Cite
|
Sign up to set email alerts
|

Association between parathyroid hormone levels and the extensiveness of coronary artery disease

Abstract: Objective:Previous studies have suggested that there is a relationship between coronary artery disease (CAD) and parathyroid hormone (PTH) levels. Here, we aimed to evaluate the association between PTH levels and severity of CAD.Methods:Patients were divided into two groups based on their serum PTH values. Patients with PTH levels ≤72 pg/mL were accepted as Group 1 (n=568) and >72 pg/mL as Group 2 (n=87). Gensini score system and >50% stenosis in any coronary artery with conventional coronary angiography were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…7,26,27 Conversely, other studies failed to confirm this association. 28,29 We previously described with the first 704 patients of this cohort, and with shorter follow-up that an interaction between the predictive value of the components of mineral metabolism may exist, as low vitamin D levels predicted cardiovascular events in the presence of high FGF23 levels, 16 but not in cases with low FGF23. Furthermore, other groups have shown that this combination is also associated with a faster progression of CKD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…7,26,27 Conversely, other studies failed to confirm this association. 28,29 We previously described with the first 704 patients of this cohort, and with shorter follow-up that an interaction between the predictive value of the components of mineral metabolism may exist, as low vitamin D levels predicted cardiovascular events in the presence of high FGF23 levels, 16 but not in cases with low FGF23. Furthermore, other groups have shown that this combination is also associated with a faster progression of CKD.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that patients with primary hyperparathyroidism have coronary microvascular dysfunction, which is completely restored after parathyroidectomy, 23 and PTH levels have been linked to the incidence and progression of CAD, 24,25 and the incidence of cardiovascular events and mortality 7,26,27 . Conversely, other studies failed to confirm this association 28,29 …”
Section: Discussionmentioning
confidence: 99%